Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Long- and Short-Term Tensile Strength and Morphology of Joined Beta-Nucleated Polypropylene Parts - Wübbeke, Andrea; Schöppner, Volker; Paul, André; Tiemann, Michael; Austermeier, Laura; Fitze, Marcus; Chen, Mingie; Jakob, Fabian; Heim, Hans-Peter; Wu, Tao; Niendorf, Thomas; Röhricht, Marie-Luise; et al. (SPE ANTEC 2020: The Virtual Edition 5)
This paper presents the results of static short-term and long-term tensile tests for beta-nucleated joined polypropylene samples by the hot plate welding process. In the present study different dimensionless joining displacements are accounted for. The results show that high short-term tensile strength does not directly transfer to high long-term tensile strength. The morphology of the weld seam in the joined samples is examined by means of transmitted and reflected light microscopy. For the dimensionless joining displacements of 0.75 and 0.95, stretched spherulites are obtained. X-Ray diffraction can be used as a tool for qualitative and quantitative analysis and eventually for differentiation of samples of various joining displacements.

Selected Aspects for the Assessment of Laser Transmission Welding - Schöppner, Volker; Wübbeke, Andrea; Schriegel, Fabian; Paul, Andrej; Tiemann, Michael; Geißler, Bastian; Schmidt, Michael; Magnier, Arnaud; Niendorf, Thomas (Joining Plastics)
In diesem Artikel werden das Scherzugverhalten und der morphologische Zustand von konturgeschweißtem Polypropylen (PP) mit einem Massenanteil von 0,2% Ruß untersucht. Dabei zeigen die Ergebnisse ...

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Straightforward Immobilization of Phosphonic Acids and Phosphoric Acid Esters on Mesoporous Silica and Their Application in an Asymmetric Aldol Reaction - Weinberger, Christian; Heckel, Tatjana; Schnippering, Patrick; Schmitz, Markus; Guo, Anpeng; Keil, Waldemar; Marsmann, Heinrich C.; Schmidt, Claudia; Tiemann, Michael; Wilhelm, René (Nanomaterials)
The combined benefits of moisture-stable phosphonic acids and mesoporous silica materials (SBA-15 and MCM-41) as large-surface-area solid supports offer new opportunities for several applications, such as catalysis or drug delivery. We present a comprehensive study of a straightforward synthesis method via direct immobilization of several phosphonic acids and phosphoric acid esters on various mesoporous silicas in a Dean–Stark apparatus with toluene as the solvent. Due to the utilization of azeotropic distillation, there was no need to dry phosphonic acids, phosphoric acid esters, solvents, or silicas prior to synthesis. In addition to modeling phosphonic acids, immobilization of the important biomolecule adenosine monophosphate (AMP) on the porous supports was also investigated. Due to the high surface area of the mesoporous silicas, a possible catalytic application based on immobilization of an organocatalyst for an asymmetric aldol reaction is discussed.

Phase Transitions of Ice in Aqueous Salt Solutions within Nanometer-Sized Pores - Jantsch, Evelyn; Weinberger, Christian; Tiemann, Michael; Koop, Thomas (The Journal of Physical Chemistry C)
We examined the effect of CaCl2 and LiCl on ice melting in mesoporous silica (MCM-41 and SBA-15 silica). For that purpose, we determined the ice melting temperature in pores of various size (pore radii between 1.9 and 11.1 nm) in water and aqueous solutions up to high total solute molality (up to about 12 mol kg–1) using differential scanning calorimetry. We found that both electrolytes reduce the ice melting temperature within the pores. An exception is the melting of ice in the smallest pores, which does not seem to be affected by the presence of solutes, most likely owing to an exclusion of the ions from entering the pores. For all other pores, we observed that the ice melting temperature decreases as a function of pore size and electrolyte concentration. Using thermodynamic considerations as well as additional experimental data we developed a parametrization that can be used to predict the ice melting point as a function of pore size and total solute molality. For that purpose, we extended a formulation of the effective water activity of aqueous solutions under mechanical pressure toward its application in confinement and tested this new parametrization on literature data.

Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (Advanced Functional Materials)
A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas-responsive electrical switch for hydrogen sulphide (H2S) detection is presented. The material can be applied as a sensitive layer for H2S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure-encoded detection limit for H2S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte-Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics.

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Copper Oxide/Silica Nanocomposites for Selective and Stable H2S Gas Detection - Paul, Andrej; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (ACS Applied Nano Materials)
A composite material of copper oxide (CuO) dispersed in the nanopores of KIT-6 silica (SiO2) is used as a dosimetric sensor for the detection of hydrogen sulfide (H2S) gas in low parts per milion concentrations. The sensor principle is based on the reversible chemical conversion of CuO to CuS, which guarantees a high selectivity, and on the corresponding percolation-induced change in electronic conductance.

Langzeitfestigkeit von Schweißungen aus PP unter Berücksichtigung der Morphologie - Schöppner, Volker; Wübbeke, Andrea; Paul, Andre; Tiemann, Michael; Fitze, F.; Austermeier, Laura; Chen, M.; Jakob, F.; Heim, H.-P.; Wu, T.; Niendorf, T.; Röhricht, M-L.; et al. (Werkstoffwoche (2019))
Langzeitfestigkeit von Schweißungen aus PP unter Berücksichtigung der Morphologie

Selective pore filling of mesoporous CMK-5 carbon studied by XRD: Comparison between theoretical simulations and experimental results - Weinberger, Christian; Hartmann, Marc; Ren, Sai; Sandberg, Thomas; Smått, Jan-Henrik; Tiemann, Michael (Microporous and Mesoporous Materials)
It is possible to infiltrate a guest species selectively in one pore system of bimodal mesoporous CMK-5 carbon by an optimized nanocasting procedure. The selective filling has a drastic impact on the low-angle X-ray diffraction pattern of this novel class of materials. The structures of CMK-5, CMK-5 composite materials (sulfur and SnO2 as guest species), and CMK-3 carbon were simulated to investigate the influence of the pore filling with different guest species on the diffraction pattern and compared with experimental results. Additionally, the impact of structural defects is taken into account. The nature of the guest species strongly influences the relative intensity of the diffraction peaks. It turns out that the diffraction patterns of sulfur-carbon composite materials are nearly identical as those of CMK-3 carbon, which is attributed to a similar electron density of carbon and sulfur. Thus, sulfur is an ideal guest species to investigate the selective pore filling in CMK-5 carbon.

Porous Aluminum Oxide and Magnesium Oxide Films Using Organic Hydrogels as Structure Matrices - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanomaterials)
We describe the synthesis of mesoporous Al2O3 and MgO layers on silicon wafer substrates by using poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel films are prepared by spreading the polymer through spin-coating, followed by photo-cross-linking and anchoring to the substrate surface. The metal oxides are obtained by swelling the hydrogels in the respective metal nitrate solutions and subsequent thermal conversion. Combustion of the hydrogel results in mesoporous metal oxide layers with thicknesses in the μm range and high specific surface areas up to 558 m2∙g−1. Materials are characterized by SEM, FIB ablation, EDX, and Kr physisorption porosimetry.

Bimodal Mesoporous CMK-5 Carbon: Selective Pore Filling with Sulfur and SnO2 for Lithium Battery Electrodes - Weinberger, Christian; Ren, Sai; Hartmann, Marc; Wagner, Thorsten; Karaman, Didem. Ş.; Rosenholm, Jessica M.; Tiemann, Michael (ACS Applied Nano Materials)
Ordered mesoporous CMK-5 carbon exhibits two distinct pore systems that can be modified individually. This work demonstrates how one of the pore systems can be selectively filled with elemental sulfur, while the other pore system remains empty. The resulting sulfur–carbon composite material with high residual porosity can be used as the cathode material in lithium–sulfur battery cells. We present a systematic investigation of the loading of CMK-5 carbon with variable relative amounts of sulfur and compare the results to the preparation of SnO2 (as well as TiO2, Mn2O3/Mn3O4, NiO) nanoparticle-loaded CMK-5 carbon.

Hydrogels as Porogens for Nanoporous Inorganic Materials - Weinberger, Christian; Kuckling, Dirk; Tiemann, Michael (Gels)
Organic polymer-hydrogels are known to be capable of directing the nucleation and growth of inorganic materials, such as silica, metal oxides, apatite or metal chalcogenides. This approach can be exploited in the synthesis of materials that exhibit defined nanoporosity. When the organic polymer-based hydrogel is incorporated in the inorganic product, a composite is formed from which the organic component may be selectively removed, yielding nanopores in the inorganic product. Such porogenic impact resembles the concept of using soft or hard templates for porous materials. This micro-review provides a survey of select examples from the literature.

Graphene oxide as flexibilizer for epoxy amine resins - Wolk, Andreas; Rosenthal, Marta; Weiß, Julia; Voigt, Markus; Wesendahl, Jan-Niklas; Hartmann, Marc; Grundmeier, Guido; Wilhelm, Rene; Meschut, Gerson; Tiemann, Michael; Bremser, Wolfgang (Progress in Organic Coatings)
Different types of reduced graphene oxide and graphene oxide particles have been studied regarding their influence on the curing behaviour of epoxy-amine resins. Especially the specific surface area of reduced graphene oxide was selectively influenced by controlled drying of the material. The different types of reduced graphene oxide particles were used to produce epoxy-amine composites that significantly change their curing behaviour and mechanical properties. A variety of surface areas and compositions were prepared by combination of a fast heating rate and different drying methods. The combination of freeze drying with a fast heating rate leads to a large specific surface area of 680 m2/g. The morphologies of the particles were observed by scanning electron microscope and the BET surface area was measured with nitrogen-physisorption. The exfoliation quality was measured by XRD. The generated graphene oxide and thermally reduced graphene oxide particles were mixed with epoxy-amine resin. The curing behaviour was studied with rheological and differential scanning calorimetry (DSC) measurements. We observed that different surface functionalities lowers the Glass transition temperature and the gel time of an epoxy-amine curing system. In addition, we found that generated graphene oxide acts as flexibilizer. An increase of the deformation from 2.5 mm to 3.1 mm was measured by Erichsen Cupping Test.

Kinetics of ozone decomposition in porous In2O3 monoliths - Klawinski, Danielle; Weinberger, Christian; Klaus, Dominik; Smått, Jan-Henrik; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
We determine ozone decomposition on indium oxide by utilizing the gas transducing properties of hierarchically porous monoliths.

Photo-Cross-Linked Polydimethylacrylamide Hydrogels as Porogens for Mesoporous Alumina - Weinberger, Christian; Chen, Zimei; Birnbaum, Wolfgang; Kuckling, Dirk; Tiemann, Michael (European Journal of Inorganic Chemistry)
Dimethylacrylamide-based hydrogels were utilized as porogenic matrices in the synthesis of mesoporous aluminum oxide (γ-Al2O3) with specific BET surface areas up to 360 m2 g–1. Polymers with molecular mass in the range 12000–35000 g mol–1 were synthesized from dimethylacrylamide and various comonomers by free-radical polymerization. Photo-cross-linking of the polymers and impregnation with aluminum nitrate [Al(NO3)3] was carried out in a single step, followed by formation of Al(OH)3/AlO(OH) and subsequent calcination. Calcination led to the formation of mesoporous Al2O3 and simultaneous combustion of the hydrogel. The structural properties of the products were characterized by powder XRD, N2 physisorption analysis, Hg intrusion porosimetry, and thermogravimetric analysis.

Organic Polymers as Porogenic Structure Matrices for Mesoporous Alumina and Magnesia - Chen, Zimei; Weinberger, Christian; Tiemann, Michael; Kuckling, Dirk (Processes)
Dimethylacrylamide-based hydrogels were utilized as porogenic matrices in the synthesis of mesoporous aluminum oxide (γ-Al2O3) with specific BET surface areas up to 360 m2 g–1. Polymers with molecular mass in the range 12000–35000 g mol–1 were synthesized from dimethylacrylamide and various comonomers by free-radical polymerization. Photo-cross-linking of the polymers and impregnation with aluminum nitrate [Al(NO3)3] was carried out in a single step, followed by formation of Al(OH)3/AlO(OH) and subsequent calcination. Calcination led to the formation of mesoporous Al2O3 and simultaneous combustion of the hydrogel. The structural properties of the products were characterized by powder XRD, N2 physisorption analysis, Hg intrusion porosimetry, and thermogravimetric analysis.

Screening of mixed-linker CAU-10 MOF materials for humidity sensing by impedance spectroscopy - Weiss, Alexander; Reimer, Nele; Stock, Norbert; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
The sorption properties of mixed-linker CAU-10 type metal organic frameworks (MOFs), [Al(OH)(1,3-BDC-X)n(1,3-BDC-SO3H)m] with 1,3-BDC = 1,3-benzenedicarboxyliate, X = H, NO2 or OH, 0.76 ≤ n ≤ 0.89 and 0.11 ≤ m ≤ 0.24, can be varied by surface modification through variation of the respective linker molecules. It is thus possible to design surface-modified CAU-10 type MOFs with variable affinity and accessibility of the pores for water vapour. When used as a dielectric in a capacitor, the MOF material will change its permittivity depending on the amount of physisorbed water; this is the working principle of capacitive humidity sensors. Three different mixed-linker compounds with CAU-10 structure are compared regarding their water sorption and impedance characteristics. A setup was developed allowing the characterization of the MOF samples under exposure to different relative humidity values in air by impedance spectroscopy. Interpretation of the results by means of standard models shows that the MOFs are qualified for functional layers of capacitive humidity sensors. Since the prepared MOFs are more temperature-stable than many commonly used polymers they offer the potential to build a new generation of high-temperature (up to 350 °C) humidity sensors.

Selective surface modification in bimodal mesoporous CMK-5 carbon - Weinberger, Christian; Cao, X.; Tiemann, Michael (Journal of Materials Chemistry A)
Ordered, bimodal mesoporous CMK-5 carbon is prepared by using mesoporous SBA-15 silica as a structural mold. The carbon material is chemically modified by oxidative treatment with acidic persulfate solution. This leads to the creation of oxygen-containing functionalities at the pore walls of the carbon (up to 13 wt% oxygen), as confirmed by IR spectroscopy. The oxidative treatment is carried out before removal of the silica mold which ensures that only one of the two distinct modes of mesopores (namely, the intra-tubular pores) is affected; the other mode (inter-tubular pores) is protected from oxidation by the presence of the silica mold. This is proven by water vapor physisorption analysis. The oxidatively treated (intra-tubular) pores are significantly more polar and, hence, better wettable than the untreated (inter-tubular) pores.

Assessment of the density of (meso)porous materials from standard volumetric physisorption data - Weinberger, Christian; Vetter, Simon; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
Characterization and application of (meso)porous materials often require information about the density of the respective samples. For example, the BET surface area is, by definition, normalized to the sample mass; hence, any comparison between samples of different composition needs to take into account their respective densities. Literature data on the densities of porous materials are scarce. Frequently, only bulk-phase densities are available which sometimes differ from those of porous samples, especially for amorphous systems, such as silica or carbon. The apparent density, i.e. the density of the sample excluding the gas-accessible pore volume, is typically determined by helium gas pycnometry utilizing specialized pycnometers. We demonstrate how to obtain the same data from standard N2 physisorption measurements as part of the regular measurement routine. We evaluate the method by reference measurements utilizing a non-porous reference sample (glass rod) to confirm the validity of the method. Then we present results on apparent density measurements of several mesoporous silica materials (MCM-41, MCM-48, SBA-15, KIT-6), mesoporous carbon (CMK-3, -5, -8, -9), and a variety of mesoporous metal oxides obtained by nanocasting.

Surface-modified CAU-10 MOF materials as humidity sensors: impedance spectroscopic study on water uptake - Weiss, Alexander; Reimer, Nele; Stock, Norbert; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
Metal–organic frameworks (MOFs) are crystalline microporous materials with tunable chemical and physical properties. By combining various metal clusters with different interconnecting organic linkers, the pore structure, crystallinity, as well as the surface properties can be modified. In the present work, modification of the organic linker molecules is utilized to synthesize CAU-10 type MOFs with variable affinity of the pore surface to water. In principle, this should influence the accessibility of the pores for water vapor and therefore offer a tool to control its sorption properties. For a deeper understanding we studied the water sorption characteristics and compared the results to the conductive and dielectric properties studied by impedance spectroscopy. Spectra in a wide frequency range from 1 mHz to 1 MHz were recorded. Data analysis is performed using the Havriliak–Negami model. The MOFs are also tested as sensitive layers for capacitive humidity sensing by correlating the change in permittivity of the materials with the amount of physisorbed water. Such an MOF-based sensor was tested with respect to environmental monitoring and compared to a commonly used commercial humidity sensor.

Synthesis of Mesoporous Metal Oxides by Structure Replication: Thermal Analysis of Metal Nitrates in Porous Carbon Matrices - Weinberger, Christian; Roggenbuck, Jan; Hanss, Jan; Tiemann, Michael (Nanomaterials)
A variety of metal nitrates were filled into the pores of an ordered mesoporous CMK-3 carbon matrix by solution-based impregnation. Thermal conversion of the metal nitrates into the respective metal oxides, and subsequent removal of the carbon matrix by thermal combustion, provides a versatile means to prepare mesoporous metal oxides (so-called nanocasting). This study aims to monitor the thermally induced processes by thermogravimetric analysis (TGA), coupled with mass ion detection (MS). The highly dispersed metal nitrates in the pores of the carbon matrix tend to react to the respective metal oxides at lower temperature than reported in the literature for pure, i.e., carbon-free, metal nitrates. The subsequent thermal combustion of the CMK-3 carbon matrix also occurs at lower temperature, which is explained by a catalytic effect of the metal oxides present in the pores. This catalytic effect is particularly strong for oxides of redox active metals, such as transition group VII and VIII metals (Mn, Fe, Co, Ni), Cu, and Ce.

Light-activated resistive ozone sensing at room temperature utilizing nanoporous In2O3 particles: Influence of particle size - Klaus, Dominik; Klawinski, Danielle; Amrehn, Sabrina; Tiemann, Michael; Wagner, Thorsten (Sensors and Actuators B: Chemical)
Ordered mesoporous In2O3 particles of variable size synthesized by the nanocasting method are used for preparation of resistive gas-sensing layers. Light activation by a LED (blue light, 460 nm) permits room-temperature ozone sensing. Apart from differences in base-line resistance in sensing layers containing small (diameter approx. 170 nm) or large particles (approx. 870 nm), differences in the response amplitude and response time constant are also observed. Signal stabilization is achieved faster for small particles. In addition, sensors show a particle size-dependent reaction threshold for low ozone concentration. Larger particles show negligible response to 50 ppb ozone whereas a significant response is observed for the small-particle sensors. A simple model based on geometrical properties and formation of depletion layers explaining the observed behavior is presented.

Nanostructured Co3O4 as a CO gas sensor: Temperature-dependent behavior - Vetter, S.; Haffer, S.; Wagner, T.; Tiemann, Michael (Sensors and Actuators B: Chemical)
Cobalt oxide spinel (Co3O4) with an ordered nanostructure is used as a resistive gas sensor for carbon monoxide (CO) in low ppm concentrations. The operating temperature has a strong impact on the concentration-dependent sensing behavior. At lower temperature (473 K) the sensor response is governed mainly by surface coverage with CO and/or CO2, whereas at higher temperature (563 K) oxygen diffusion in the crystal lattice of Co3O4 strongly affects the sensing behavior.

Synthesis of mesoporous alumina through photo cross-linked poly(dimethylacrylamide) hydrogels - Birnbaum, Wolfgang; Weinberger, Christian; Schill, Verena; Haffer, Stefanie; Tiemann, Michael; Kuckling, Dirk (Colloid and Polymer Science)
Catalysis plays a central role in many fields of life, e.g., in biochemical processes, to reduce energy costs and resources in chemical industry and to decrease or even avoid environmental pollution and in energy management. Porous alumina (Al2O3) is an essential material in various applications, especially as a support material for catalysts. It is often prepared by nanocasting using porous carbon materials that serve as rigid structure matrices. In this work, an alternative way to synthesize mesoporous Al2O3 by using hydrogels as porogenic material is presented. Hydrogels can easily be patterned by light and used to imprint their structure onto alumina opening a new approach to fabricate patterned Al2O3. The hydrogels used in this work are based on poly(dimethylacrylamide) and were photo-chemically cross-linked. Followed by a nanocasting process, mesoporous alumina samples were synthesized and characterized by N2 physisorption and X-ray diffraction. The cross-linker amount in the polymer network was varied and the influence on the properties of the Al2O3 is analyzed.

A synthesis concept for a nanostructured CoFe2O4/BaTiO3 composite: Towards multiferroics - Haffer, Stefanie; Lüder, Christian; Walther, Till; Köferstein, Roberto; Ebbinghaus, Stefan G.; Tiemann, Michael (Microporous and Mesoporous Materials)
The synthesis of a periodically ordered, nanostructured composite consisting of CoFe2O4 and BaTiO3 is presented. In a first step, mesoporous CoFe2O4 is prepared by the structure replication method (nanocasting) using mesoporous KIT-6 silica as a structural mold. Subsequently, BaTiO3 is created inside the pores of CoFe2O4 by the citrate route, resulting in a well-ordered composite material of both phases. The two components are known for their distinct ferroic properties, namely ferrimagnetism (CoFe2O4) and ferroelectricity (BaTiO3), respectively. Therefore, this proof of synthesis concept offers new perspectives in the fabrication of composite materials with multiferroic properties.

One-step synthesis of multi-modal pore systems in mesoporous In2O3: A detailed study - Klaus, Dominik; Amrehn, Sabrina; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
Ordered mesoporous silica phases (e.g. KIT-6, SBA-15) are used as structure matrices for negative replica structures of mesoporous In2O3. We present a detailed study on how the controlled synthesis of mono-, bi- and trimodal pore systems in the products is accomplished by systematic variation of the procedure of infiltrating a precursor species (In(NO3)3) into the pores of the silica matrix and subsequent thermal conversion into In2O3. Melt impregnation and conversion in a closed reactor facilitates a one-step casting process for ordered mesoporous indium oxide (In2O3). We present a model based on variation of the pore filling.

New Sensing Model of (Mesoporous) In2O3 - Wagner, Thorsten; Donato, Nicola; Tiemann, Michael (Springer Series on Chemical Sensors and Biosensors)
Recently indium oxide (In2O3) attracted attention as a material for sensing layers in semiconducting gas sensors. Compared to frequently investigated materials like tin dioxide (SnO2), tungsten trioxide (WO3), or gallium oxide (Ga2O3) indium oxide offers some unique properties. The most prominent one is its selectivity to oxidizing gases such as ozone (O3) or nitrogen dioxide (NO2) at low operating temperatures (<150°C). Combined with the photoreduction properties of nanocast, porous In2O3 highly selective sensing layers with a fast response can be prepared. In some cases even room temperature measurements are possible; therefore this material allows for designing low-power sensors without the need for special sensor substrates (e.g., μ-hotplates). Detailed analysis of the sensing mechanism reveals that known sensing models are not able to describe the observed effects. Therefore a new sensing model for ordered nanoporous In2O3 is presented which will be applicable for nonstructured material too.

Arduino-Based Shield for Resistive Gas Sensor Array Characterization Under UV Light Exposure - Aloisio, D.; Donato, N.; Neri, G.; Latino, M.; Wagner, T.; Tiemann, Michael; Capra, P. P. (Lecture Notes in Electrical Engineering)
In this paper, the development and validation of a shield prototype for resistive sensor array characterization with Arduino UNO, a platform based on ATmega328 microcontroller provided by ATMEL, is reported. The resistance variation of the sensor can be evaluated by properly choosing the capacitance value and by measuring the period (frequency) of a custom inverter-based oscillator. The GUI and the developed firmware are able to perform the real-time monitoring of the sensor responses. The developed shield is able to measure the response of up to six sensors under UV radiation by means of LED devices. First results carried out with resistive sensors based on mesoporous In2O3-based material under UV light exposure are reported.

Fructose as a Precursor for Mesoporous Carbon: Straightforward Solvent-Free Synthesis by Nanocasting - Weinberger, Christian; Haffer, S.; Wagner, T.; Tiemann, Michael (ACS Symposium Series)
Due to their unique properties, ordered mesoporous carbon (OMC) materials prepared by nanocasting have raised great attention in recent years. Their synthesis usually comprises multiple cycles of impregnating a porous structure matrix with an aqueous solution of a suitable precursor, such as sucrose or other, often hazardous, compound. We present a more straightforward variation of this method by using fructose as the precursor compound. By using a solvent-free melt of the precursor, the impregnation requires only a single step. After carbonization by thermal decomposition and removal of the mesoporous silica structure matrix (SBA-15), ordered mesoporous carbon with one (CMK-3) or two (CMK-5) pore modes in two-dimensional, hexagonal symmetry (p6mm) is obtained.

Nanoporous Materials: Synthesis Concepts and Model Experiments for School Chemistry Education - Wilke, Timm; Haffer, Stefanie; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten; Waitz, Thomas (Journal of Nano Education)
Nanoporous Materials, like carbons, silica and semiconducting metal oxides, play a major role in recent scientific research, especially in the fields of energy storage, catalysis, material separation and sensor technology. Thus, our aim is to focus on simple synthesis concepts for these materials, such as soft matter templating or nanocasting, which can be easily introduced by means of appropriate models in school chemistry education or school laboratories. In addition to facile and realizable syntheses in school, several experiments concerning catalysis and gas sensing will be presented, too. By these experiments the characteristics of nanoporous materials can be obviously demonstrated and additionally, these experiments can serve as a starting point for further experiments that could easily be developed by students themselves, particularly in relation to environmental issues.

Fructose and Urea as Precursors for N-/O-Modified Mesoporous Carbon with Enhanced Sorption Capacity for Heavy Metal Ions - Weinberger, Christian; Haffer, Stefanie; Wagner, Thorsten; Tiemann, Michael (European Journal of Inorganic Chemistry)
Ordered mesoporous carbon with a high heteroatom (N, O) content was prepared by nanocasting from a melt of a eutectic mixture of fructose and urea (60/40 wt.-%; melting temperature ca. 65 °C). These precursor compounds are cheap and environmentally friendly. The material possesses enhanced pore-wall surface polarity as compared to that of mesoporous carbon prepared by the same technique without urea. This was verified by water sorption analysis. As a result, the heteroatom-modified material shows higher sorption capacity for the uptake of heavy metal ions (Cu2+) from aqueous solution, which may be interesting for potential application in wastewater cleaning.

UV light-enhanced NO2 sensing by mesoporous In2O3: Interpretation of results by a new sensing model - Wagner, Thorsten; Kohl, Claus-Dieter; Malagù, Cesare; Donato, Nicola; Latino, Mariangela; Neri, Giovanni; Tiemann, Michael (Sensors and Actuators B: Chemical)
The light-enhanced NO2 sensing behavior of mesoporous In2O3 is measured and interpreted by means of a new sensing model. The model aims at explaining (i) the drop in electronic resistance of n-type semiconducting In2O3 under UV light exposure, (ii) the light-enhanced reaction to oxidizing gases, and (iii) the faster reaction and regeneration in mesoporous In2O3 as compared to non-porous material. Contrary to the conventional double Schottky model the dominating factor for the change in resistance is a change of oxygen vacancy donor states (0.18 eV below the conduction band) in the bulk phase due to photoreduction, instead of chemisorption. For the faster reaction and regeneration we propose an explanation based on enhanced oxygen diffusion in the In2O3 crystal lattice, specifically dominant in the mesoporous structure. The response of ordered mesoporous In2O3 to NO2 is stronger than in case of unstructured bulk material (with an average grain size of ca. 40 nm). The reaction is significantly accelerated by illuminating the samples with UV light. However, the response of the mesoporous material is weaker in the illuminated case.

Nanostructure-Related Magnetic Properties of Various Mesoporous Cobalt Oxide and Cobalt Ferrite Spinel Phases - Haffer, Stefanie; Walther, Till; Köferstein, Roberto; Ebbinghaus, Stefan G.; Tiemann, Michael (The Journal of Physical Chemistry C)
Nanostructure-related magnetic properties are investigated systematically for various mesoporous cobalt oxide (Co3O4) and cobalt ferrite (CoFe2O4) spinel phases. Synthesis of the materials by nanocasting offers the opportunity to obtain materials which are different from each other with respect to both specific surface area and crystallite size. As a result, the respective contributions of two types of interfaces, namely, “solid–gas” and “solid–solid” interfaces, to the magnetic ordering can be distinguished. Structural characterization of the porous materials by X-ray diffraction, N2 physisorption, and electron microscopy as well as investigation of the magnetic behavior (field-dependent magnetization and temperature-dependent susceptibility) are presented.

Mesoporous materials as gas sensors - Wagner, Thorsten; Haffer, Stefanie; Weinberger, Christian; Klaus, Dominik; Tiemann, Michael (Chem. Soc. Rev.)
Ordered mesoporous materials have great potential in the field of gas sensing. Today various template-assisted synthesis methods facilitate the preparation of silica (SiO2) as well as numerous metal oxides with well-defined, uniform and regular pore systems. The unique nanostructural properties of such materials are particularly useful for their application as active layers in gas sensors based on various operating principles, such as capacitive, resistive, or optical sensing. This review summarizes the basic aspects of materials synthesis, discusses some structural properties relevant in gas sensing, and gives an overview of the literature on ordered mesoporous gas sensors.

NO2 Sensors with Reduced Power Consumption Based on Mesoporous Indium Oxide - Donato, Nicola; Wagner, Thorsten; Tiemann, Michael; Waitz, Thomas; Kohl, Claus-Dieter; Latino, Mariangela; Neri, Giovanni; Spadaro, Donatella; Malagù, Cesare (Lecture Notes in Electrical Engineering)
We report on sensing properties of ordered mesoporous nanostructures of In2O3 synthesized by nanocasting procedure towards NO2. The nanostructured material shows improved recover times and higher responses compared to non nanostructured material at low operating temperatures (100–150°C) thus allowing the use for low power NO2 sensors. These properties may be related to fast oxygen in and out propagation facilitated by an enhanced surface accessibility of the nanostructure.

Photoreduction of Mesoporous In2O3: Mechanistic Model and Utility in Gas Sensing - Wagner, Thorsten; Kohl, Claus-Dieter; Morandi, Sara; Malagù, Cesare; Donato, Nicola; Latino, Mariangela; Neri, Giovanni; Tiemann, Michael (Chemistry - A European Journal)
A model is proposed for the drop in electronic resistance of n-type semiconducting indium oxide (In2O3) upon illumination with light (350 nm, 3.5 eV) as well as for the (light-enhanced) sensitivity of In2O3 to oxidizing gases. Essential features of the model are photoreduction and a rate-limiting oxygen-diffusion step. Ordered, mesoporous In2O3 with a high specific surface area serves as a versatile system for experimental studies. Analytical techniques comprise conductivity measurements under a controlled atmosphere (synthetic air, pure N2) and temperature-resolved in-situ Fourier transform infrared (FTIR) spectroscopy. IR measurements reveal that oxygen vacancies form a donor level 0.18 eV below the conduction band.

Mesoporöse Silica - Moderne Funktionsmaterialien im Chemieunterricht - Wilke, Timm; Haffer, Stefanie; Tiemann, Michael; Waitz, Thomas (CHEMKON)
Poröse Funktionsmaterialien wie halbleitende Metalloxide, Kohlenstoff-Formen oder auch Silica werden aktuell von verschiedenen Wissenschaftsdisziplinen intensiv für Bereiche der Energiespeicherung, Sensorik, Katalyse und Stofftrennung erforscht. Im Beitrag werden schwerpunktmäßig geordnet-mesoporöse Silica-Materialien behandelt, die seit etwa 20 Jahren synthetisch zugänglich sind. Neben den Grundlagen der Herstellung über ein Templat-Verfahren werden im Beitrag auch drei Experimente vorgestellt, die im Chemieunterricht oder Schülerlabor durchgeführt werden können. Zudem wird gezeigt, dass sich verschiedene Aspekte aus dem Kompetenzbereich Fachwissen mit Hilfe des Themas „Mesoporöse Silica“ miteinander vernetzen lassen.

Mesoporous Al2O3 by Nanocasting: Relationship between Crystallinity and Mesoscopic Order - Haffer, Stefanie; Weinberger, Christian; Tiemann, Michael (European Journal of Inorganic Chemistry)
Crystalline, mesoporous alumina (Al2O3) materials with specific surface areas up to 400 m2 g–1 have been synthesized by means of structure replication (nanocasting) using CMK-8 carbon as a structure matrix. A crucial step during this synthesis procedure is the conversion of aluminum nitrate into aluminum hydroxide by treatment with ammonia vapor. The impact of this step was investigated in some detail. Prolonged vapor treatment has a positive impact on the crystallinity of the final Al2O3 products but at the same time leads to loss of mesoscopic structural order and porosity.

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

X-ray absorption near-edge spectroscopy investigation of the oxidation state of Pd species in nanoporous SnO2 gas sensors for methane detection - Wagner, T.; Bauer, M.; Sauerwald, T.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report the correlation of the aging of Pd-doped SnO2 methane sensors with the change of the oxidation state of Pd. Mesoporous SnO2 doped with palladium species was prepared and exposed to different gas mixtures at high temperature (600 °C) to simulate long term usage. After each exposure step a fraction of the sample was cooled down to “freeze” the current oxidation state of Pd which was then analyzed by X-ray Absorption Near-Edge Spectroscopy (XANES) using the 'white line' (i.e. the absorption peak corresponding to the transition from the 2p3/2 core level to unoccupied 4 d states) intensity of the L(III) edge as a probe for the oxidation state. The Pd oxidation state correlates with the response of the resistive SnO2 sensor to methane gas, as determined by measuring the gas response to different concentrations of methane. Samples treated with 5000 ppm methane in air show a significant reduction of Pd(II) to Pd(0), depending clearly on the carrier gas (synthetic air, pure nitrogen) and on the temperature (600 °C vs. 300 °C).

A High Temperature Capacitive Humidity Sensor Based on Mesoporous Silica - Wagner, Thorsten; Krotzky, Sören; Weiß, Alexander; Sauerwald, Tilman; Kohl, Claus-Dieter; Roggenbuck, Jan; Tiemann, Michael (Sensors)
Capacitive sensors are the most commonly used devices for the detection of humidity because they are inexpensive and the detection mechanism is very specific for humidity. However, especially for industrial processes, there is a lack of dielectrics that are stable at high temperature (>200 °C) and under harsh conditions. We present a capacitive sensor based on mesoporous silica as the dielectric in a simple sensor design based on pressed silica pellets. Investigation of the structural stability of the porous silica under simulated operating conditions as well as the influence of the pellet production will be shown. Impedance measurements demonstrate the utility of the sensor at both low (90 °C) and high (up to 210 °C) operating temperatures.

Micrometer-sized nanoporous tin dioxide spheres for gas sensing - Smått, J.-H.; Lindén, M.; Wagner, T.; Kohl, C.-D.; Tiemann, Michael (Sensors and Actuators B: Chemical)
We report the synthesis of mesoporous tin dioxide (SnO2) materials with well-defined particle morphology. The products consist of uniform spheres with a diameter of 5 μm. The spheres are hierarchically porous with two distinct pore modes of 5.0 nm and 52 nm, respectively. This special porosity is the result of a synthesis procedure which involves a ‘hard templating’ (nanocasting) process. The product forms an approximately homogeneous monolayer of spheres on a sensor substrate and shows promising response to methane gas with low cross-sensitivity to water. The structural properties and gas-sensing performance are compared with a mesoporous SnO2 material without defined morphology, prepared by a ‘soft templating’ procedure.

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

Accessing Ultrashort Reaction Times in Particle Formation with SAXS Experiments: ZnS Precipitation on the Microsecond Time Scale - Schmidt, Wolfgang; Bussian, Patrick; Lindén, Mika; Amenitsch, Heinz; Agren, Patrik; Tiemann, Michael; Schüth, Ferdi (Journal of the American Chemical Society)
Precipitation of zinc sulfide particles is a very rapid process, and monitoring of the particle growth is experimentally very demanding. Applying a liquid jet flow cell, we were able to follow zinc sulfide particle formation on time scales down to 10−5 s. The flow cell was designed in such a way that data acquisition on the microsecond time scale was possible under steady-state conditions along a liquid jet (tubular reactor concept), allowing SAXS data accumulation over a time scale of minutes. We were able to monitor the growth of zinc sulfide particles and found experimental evidence for very rapid particle aggregation processes within the liquid jet. Under the experimental conditions the particle growth is controlled by mass transfer: i.e., the diffusion of the hydrogen sulfide into the liquid jet.